(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Bones that break easily might point to osteogenesis imperfecta, often called brittle bone disease. Not all cases look the same - one person’s experience can differ greatly from another’s. What ties them together is weak bones, thin structure inside the skeleton, and breaks happening without much force. Though broken bones get the most attention, the problem goes beyond just the frame of the body. Type I collagen fails at its job; this protein normally gives strength to bone, skin, teeth, eyes, and more. When it does not form right, tissues relying on it start to struggle. Some people notice their whites of the eyes are bluish. Others deal with hearing loss, loose joints, or teeth that chip and stain quickly. Heart issues sometimes appear. Breathing may become harder over time. Each symptom links back to flawed support within the body’s makeup.